Impact of Inclusion of Information and Communication Technologies in School Facilities and Effective Learning of Students in Green School - Verma, Rekha; Sharma, Naveen (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Future leaders of the nation, teachers and students are progressively exposed to think about sustainable practices and challenges in schools around the world to reconsider and redefine their missions, to modify and restructure their teaching and learning practices and campus life. Despite the increasing quantity of research on green schools, there has been comparatively less published literature about how teachers and learners in a green school use technology enabled methodology, especially from a holistic point of view. This study focuses on how school facilities use technology-enabled learning that might improve learning outcomes and health & well-being as an essential component of learning in Green Schools. 21 personal interviews were conducted as part of this study, which employed a case-based methodology. The target age group was determined and the age group of the selected students was set at thirteen to fourteen years, who were studying in seventh and eighth grade. The data collected by personal interviews was analyzed by using Leximancer tool. It was perceived that the facilities offered by Green schools are profoundly beneficial for affecting the learning outcomes by influencing the attitude of students. By providing context for our observations, we emphasize and conclude that as a learning platform green schools, can help to affect children's mood and thus improve their learning outcomes while maintaining their physical, mental, emotional, and social well-being. In nutshell, the results would apprise and assist decision-makers including policy-makers, building specialists, architects and teachers in designing green strategies and polices for Green schools.